2013
DOI: 10.1007/s10597-013-9609-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Depression Referrals in Older People

Abstract: Seasonal affective disorder is becoming more widely recognised as a prevalent mood disorder in the adult population. However, few studies have investigated the link between sunlight exposure and mood in the elderly. Referrals to the community Mental Health Care for Older People (MHCOP) in the Hackney and City area, were screened for the number of patients referred with depression in three separate years (2007, 2009 and 2011) in order to determine whether more referrals were made to the service during darker mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
3
1
1
Order By: Relevance
“…Furthermore, to the best of our knowledge we are the first study to look at the effect of climate specifically in this age group. Our results however conflict with some prior studies in older adults (de Craen et al, 2005;Holloway and Evans, 2014). The Leiden Study previously reported a null finding in relation to the relationship between mood and local weather in the over 85's and had the advantage of a longitudinal design (de Craen et al, 2005).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, to the best of our knowledge we are the first study to look at the effect of climate specifically in this age group. Our results however conflict with some prior studies in older adults (de Craen et al, 2005;Holloway and Evans, 2014). The Leiden Study previously reported a null finding in relation to the relationship between mood and local weather in the over 85's and had the advantage of a longitudinal design (de Craen et al, 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the Leiden study focused solely on a select group of the oldest old (all of whom were born in the same year and lived in a single city in Holland), had a smaller sample size and did not assess the impact of long-term climate. A small non-representative, cross-sectional study investigating seasonality of psychiatric referrals in older adults to a catchment area in the UK, also reported that there were no significant relationships (Holloway and Evans, 2014). Such discrepancies in findings may be accounted for by differences in sample size, our use of a population representative sample or alternatively by our use of objective weather data mapped to the individual's location.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study has showed no significant seasonal pattern of depressive symptoms among the general population (Kerr et al, 2013). Aptly, Holloway and Evans (2013) observed no seasonal variation of depressive episodes among a population of older people. In our study, a seasonality of admissions in patients with recurrent depression and single depressive episode was observed with peaks in March and November for recurrent depression, and in May and September for a single depressive episode.…”
Section: Discussionmentioning
confidence: 91%
“…(2013), all were registry studies. Six of them (Cerbus and Dallara, 1975; Christensen and Dowrick, 1983; Posternak and Zimmerman, 2002; Belleville et al ., 2013; Holloway and Evans, 2014) found no indications of seasonality, including Sato et al . (2006) that found no overall association, but higher rates of prescriptions for major depressive episode in spring among individuals with unipolar depression without depressed mixed states, and in autumn for bipolar and unipolar individuals with depressed mixed states.…”
Section: Resultsmentioning
confidence: 98%